Innovation and New Path Creation: The Role of Niche Environments in the Development of the Wind Power Industry in Germany and the UK - Carpenter, Juliet; Simmie, James; Conti, Elisa; Povinelli, Fabiana; Kipshagen, Joschka Milan (European Spatial Research and Policy, 2013)
This paper seeks to explore the issues of innovation and new path creation in the UK and Germany, illustrated through the case of the modern wind power industry. Taking an evolutionary perspective drawing on path dependence theory, the paper examines the role of niche environments in the creation of new economic pathways. The research finds that new economic pathways are more likely to develop in places where niche conditions provide receptive environments for innovations to flourish. The policy implications of the research include the importance of supporting niche environments that encourage growth in new sectors and the need for financial support to bring innovations to market, to encourage the development of new economic pathways.